DNA Methylation Involved in Pepper (Capsicum annuum L.)Fruit Ripening Regulation and Interacts with Phytohormones. - Xiao, K.; Chen, J.; He, Q.; Wang, Y.; Shen, H.; Sun, L.
There is growing evidence to suggest that epigenetic tags, especially DNA methylation, are critical regulators of fruit ripening. To examine whether this is the case in sweet pepper (Capsicum annuum)we conducted experiments at the transcriptional, epigenetic, and physiological levels. McrBC PCR, bisulfite sequencing, and real-time PCR demonstrated that DNA hypomethylation occurred in the upstream region of the transcription start site of some genes related to pepper ripening at the turning stage, which may be attributed to up-regulation of CaDML2-like and down-regulation of CaMET1-like1, CaMET1-like2, CaCMT2-like, and CaCMT4-like. Silencing of CaMET1-like1 by virus-induced gene silencing led to DNA hypomethylation, increased content of soluble solids, and accumulation of carotenoids in the fruit, which was accompanied by changes in expression of genes involved in capsanthin/capsorubin biosynthesis, cell wall degradation, and phytohormone metabolism and signaling. Endogenous ABA increased during fruit ripening, whereas endogenous IAA showed an opposite trend. No ethylene signal was detected during ripening. DNA hypomethylation repressed the expression of auxin and gibberellin biosynthesis genes as well as cytokinin degradation genes, but induced the expression of ABA biosynthesis genes. In mature-green pericarp, exogenous ABA induced expression of CaDML2-like but repressed that of CaCMT4-like. IAA treatment promoted the transcription of CaMET1-like1 and CaCMT3-like. Ethephon significantly up-regulated the expression of CaDML2-like. Treatment with GA3 and 6-BA showed indistinct effects on DNA methylation at the transcriptional level. On the basis of the results, a model is proposed that suggests a high likelihood of a role for DNA methylation in the regulation of ripening in the non-climacteric pepper fruit.
Keywords: CAROTENOIDS; DNA METHYLATION; FRUIT RIPENING; GENE EXPRESSION; PEPPER; PLANT HORMONE